The Effect of Earnings Management on Dividend Policy: Concentrated Ownership and Audit Committee Expertise as Moderating Variables - Anggraini, Shabira Dwi; Suranta, Eddy; Midiastuty, Pratana Puspa (Ilomata International Journal of Tax and Accounting, 2024)
Dividend policy is one of the important decisions of a firm where this dividend policy is an important consideration for shareholders as an indicator of the firms success in managing the capital invested by investors. This study aims to provide empirical evidence of how earnings management affects dividend policy, then whether concentrated ownership and audit committee expertise can affect the relationship between earnings management and dividend policy. The research sample is a manufacturing company with a period of 2018-2022. The sample selection used a purposive sampling approach so that the total observations amounted to 128 observations. The results showed that earnings management has a remarkable effect on dividend coverage, concentrated ownership and audit committee expertise can affect the relationship between earnings management and dividend policy in an effective way. The effect proves that managers have the discretion to choose accounting methods to file better earnings as a way to signal the success of the firms management and on the other hand earnings control benefits focused ownership so that earnings management and concentrated ownership are complementary. This observation contributes to signal theory and firm theory in explaining the earnings control movement and focused ownership as moderating variables in explaining the relationship between earnings management and dividend coverage. The real implication of this research is that it can be used as a consideration for firms in making decisions regarding the proportion of dividends distributed, and can be a review tool for investors in investing.